Analysis of English teaching materials with gender equality perspective at junior high school - Kriswanda Krishnapatria; Hilmansyah Saefullah (Jurnal Pendidikan dan Pengajaran, 2019)
This study was carried out to disclose the gender bias issue by analysing English teaching materials. The research objects are three textbooks used by junior high school students from 7th to 9th grade in learning English at one school in Karawang. This is a qualitative research implementing content analysis to obtain the findings. From the outcomes of the research, it shows clearly that the three books have only delivered very little value of gender equality within the contents, in which gender stereotype dominantly become the primary issue. As a result, it is necessary for English teaching materials at junior high school level to be adjusted and revised with more balanced contents of gender equality perspective.